Current Strategies for the Manufacture of Small Size Tissue Engineering Vascular Grafts - Carrabba, Michele; Madeddu, Paolo (Frontiers in Bioengineering and Biotechnology, 2018)
Occlusive arterial disease, including coronary heart disease and peripheral arterial disease, is the main cause of death, with an annual mortality incidence predicted to rise to 23.3 million worldwide by 2030. Current revascularization techniques consist of angioplasty, placement of a stent, or surgical bypass grafting. Autologous vessels, such as the saphenous vein and internal thoracic artery, represent the gold standard grafts for small-diameter vessels. However, they require invasive harvesting and are often unavailable. Synthetic vascular grafts represent an alternative to autologous vessels. These grafts have shown satisfactory long-term results for replacement of large- and medium-diameter arteries, such as the carotid or common femoral artery, but have poor patency rates when applied to small-diameter vessels, such as coronary arteries and arteries below the knee. Considering the limitations of current vascular bypass conduits, a tissue-engineered vascular graft (TEVG) with the ability to grow, remodel, and repair in vivo presents a potential solution for the future of vascular surgery. Here, we review the different methods that research groups have been investigating to create TEVGs in the last decades. We focus on the techniques employed in the manufacturing process of the grafts and categorize the approaches as scaffold-based (synthetic, natural, or hybrid) or self-assembled (cell-sheet, microtissue aggregation and bioprinting). Moreover, we highlight the attempts made so far to translate this new strategy from the bench to the bedside.